Strategi Pemasaran Produk “Tempe Samodra” Kelurahan Mojosongo, Kecamatan Jebres, Kota Surakarta - Andi Nadhira Gayatri Amarala; Suprapti Supardi; Mohammad Harisudin (Universitas Muhammadiyah Malang, 2020)
Tempe Samodra is one of the industries that produce tempe since 1985 in the city of Surakarta. This study aims to identify and formulate internal and external factors that will be faced by Tempe Samodra, formulate alternative strategies that can be done for marketing Tempe Samodra products, and determine alternative priorities that can be done for marketing Tempe Samodra products. The basic method used is the descriptive-analytical method. The method of selecting research locations is done intentionally (purposive) and determining respondents using key informants. Data analysis methods used include (1) IFE and EFE Matrix, (2) Grand Strategy Matrix, (3) SWOT Matrix, (4) QSPM. The results showed that Tempe Samodra was in quadrant I in the Grand Strategy matrix. Alternative Strategies that can be applied based on the SWOT matrix are SO (strength-opportunity) strategies. Priority alternative strategies preferred in marketing Tempe Samodra products based on QSPM are introducing and promoting Tempe Samodra products to traders and consumers with a total attractiveness value of 6.215.